Associations between commute mode and cardiovascular disease, cancer, and all-cause mortality, and cancer incidence, using linked Census data over 25 years in England and Wales: a cohort study. Issue 5 (May 2020) - Patterson, Richard; Panter, Jenna; Vamos, Eszter P; Cummins, Steven; Millett, Christopher; Laverty, Anthony A
Summary: Background: Active travel is increasingly recognised as an important source of physical activity. We aimed to describe associations between commute mode and cardiovascular disease, cancer, and all-cause mortality. Methods: We analysed data from the Office for National Statistics Longitudinal Study of England and Wales (ONS-LS), which linked data from the Census of England and Wales (henceforth referred to as the Census) for 1991, 2001, and 2011 to mortality and cancer registrations. The cohort included individuals traced in the ONS-LS who were economically active (ie, aged ≥16 years, not retired from work, and not a full-time carer). Commuting by private motorised transport, public transport, walking, and cycling were compared in terms of all-cause mortality, cancer mortality, cardiovascular disease mortality, and cancer incidence, using Cox proportional-hazards models with time-varying covariates. Models were adjusted for age, sex, housing tenure, marital status, ethnicity, university education, car access, population density, socioeconomic classification, Carstairs index quintile, long-term illness, and year entered the study, and were additionally stratified by socioeconomic group. Findings: Between the 1991 Census and the 2011 Census, 784 677 individuals contributed data for at least one Census, of whom 394 746 were included in the ONS-LS and were considered to be economically active working-age individuals. 13 983 people died, 3172 from cardiovascular disease and 6509 from cancer, and there were 20 980 incident cancer cases. In adjusted models, compared with commuting by private motorised vehicle, bicycle commuting was associated with a 20% reduced rate of all-cause mortality (hazard ratio [HR] 0·80, 95% CI 0·73–0·89), a 24% decreased rate of cardiovascular disease mortality (0·76, 0·61–0·93), a 16% lower rate of cancer mortality (0·84, 0·73–0·98), and an 11% reduced rate of incident cancer (0·89, 0·82–0·97). Compared with commuting by private motorised vehicle, rail commuters had a 10% lower rate of all-cause mortality (HR 0·90, 95% CI 0·83–0·97) and a 21% decreased rate of cardiovascular disease mortality (0·79, 0·67–0·94), in addition to a 12% reduced rate of incident cancer (0·88, 0·83–0·94). Walk commuting was associated with 7% lower cancer incidence (HR 0·93, 95% CI 0·89–0·97) Stratified analyses did not indicate differences in associations between socioeconomic groups. Interpretation: Our findings augment existing evidence for the beneficial health effects of physically active commute modes, particularly cycling and train use, and suggest that all socioeconomic groups could benefit. Funding: National Institute for Health Research.